Applications, benefits and challenges of telehealth in India during COVID-19 pandemic and beyond: a systematic review - Eslavath Rajkumar; Aswathy Gopi; Aditi Joshi; Aleena Elizabeth Thomas; N. M. Arunima; Gosetty Sri Ramya; Prachi Kulkarni; P. Rahul; Allen Joshua George; John Romate; John Abraham (BMC, 2023)
Abstract Background India, the seventh-largest country in the world and the second-most populated faces enormous challenges when it comes to healthcare. The country's healthcare system was close to collapse due to the detrimental effects of the COVID-19 pandemic. Telehealth, which enables treating patients remotely, played a critical role during these challenging times. This systematic review investigates in detail the role of telehealth during COVID-19 and its application beyond the pandemic. Methods Database searches on PubMed, Scopus, Science Direct and Web of Science were carried out for studies published on telehealth, and articles were included if they focused on any audio or video telehealth consultation during the pandemic in India. Findings were synthesised into three main themes: applications, benefits and challenges of telehealth services. Methodological quality was assessed using JBI critical appraisal tools. Results The initial search on databases yielded 1143 articles. Of those, 19 met the eligibility criteria. Findings highlight the effective utilisation of telehealth across multiple medical specialities. Although insufficient technological infrastructure and other barriers due to the virtual consultation challenge the successful implementation of telehealth in India, it has the potential to bridge the rural-urban healthcare divide with cost-effective and easily accessible services. Conclusion High patient/provider satisfaction underscores the need to integrate telehealth into routine healthcare practices in the country. However, the review urges the government and healthcare practitioners to address the telehealth challenges with prime importance to ensure quality healthcare throughout the nation even after the pandemic.